BUDAYA POLITIK PEREMPUAN SEMENDE DI KABUPATEN OGAN KOMERING ULU SELATAN - Alip Susilowati Utama (SOSIALITA, 2018)
This thesis discusses cultural and political culture in ethnic Semende on matrilineal kinship system. The ethnic Semende spread in several districts in Ogan Komering Ulu Selatan has strong ties to customary that leads the attitudes and behavior community based on the customary. Research conducted since December 2015 until April 2016 aims to analyze the relationship between matrilineal culture and the cultural construction of political culture women Semende and analyze the cause of the differences in the roles of women Semende at elite and grassroots level. This study used a qualitative approach with the informant traditional leaders and women Semende from the grassroots and the elite of society. The results of the interview subsequently processed and analyzed as a result of research. The results showed that the matrilineal culture of the Construction ethnic Semende influence on the mindset of women Semende but gave no influence on the political culture towards women Semende participant political culture. This occurs because the bonds formed in the indigenous ethnic Semende very strong.With a degree of viscosity customary in Semende society, the participation rate of women Semende against small groups at lower layers of society becomes higher. But the same thing does not happen to women in elites. The fact that support of matrilineal in Semende society does not create women become the center of power on the wider environment. This proves that even in a matrilineal society, the tendency towards patriarchy still high and became barriers cultural in the Women’s political culture.